LOBBY AND THE INFLUENCE POWER FROM THE PUBLIC AGENTS’ VIEW (Dimensión Empresarial, 2019)
The present research aims at exploring and deepening the knowledge about lobby and the influence power from pressure groups along to public agents in favour of the consumer. This qualitative work used a semi-structured interview as a data collecting tool. The results were processed and analysed through the content analysis technique, presented by analysis categories and subcategories. Based on the investigation, it was concluded that the pressure group and lobby activities presented themselves as vital for the acquisition of hypercompetitive advantages, and that the persuasion that originates from privileged information benefits the end consumer.